2006
DOI: 10.1248/bpb.29.655
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics of Kojic Acid on Gene Expression Profiling of A375 Human Malignant Melanoma Cells

Abstract: Kojic acid is a natural product and normally used as a food additive and preservative, a skin-whitening agent in cosmetics, a plant growth regulator and a chemical intermediate. Using DNA microarray technology, the overall biological effects of kojic acid on the gene expression profiling of a human skin A375 malignant melanoma cells were examined. After treatment with kojic acid, a total of 361 differentially expressed genes were distinctively changed with 136 up-regulated genes and 225 down-regulated genes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 73 publications
(78 reference statements)
1
33
0
1
Order By: Relevance
“…The selected genes were validated by RT-qPCR analysis to confirm the microarray data. RT-qPCR results showed the gene expression levels of seven expressed genes in kojic acidstimulated A375 melanoma cells agreed with the DNA microarray expression data 18 . One gene chosen for RT-qPCR examination was the apolipoprotein B RNA editing deaminase (APOBEC1) gene 25 .…”
Section: Rt-qpcr Validation Of Microarray Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…The selected genes were validated by RT-qPCR analysis to confirm the microarray data. RT-qPCR results showed the gene expression levels of seven expressed genes in kojic acidstimulated A375 melanoma cells agreed with the DNA microarray expression data 18 . One gene chosen for RT-qPCR examination was the apolipoprotein B RNA editing deaminase (APOBEC1) gene 25 .…”
Section: Rt-qpcr Validation Of Microarray Resultssupporting
confidence: 67%
“…However, we will further study the effects of kojic acid on biological and molecular mechanisms in human melanoma skin cells, including in other parts of the body, and also examine other biological functions of kojic acid in its cosmetic and/or therapeutic applications. We also examined the effect of different arbutin concentrations on the growth inhibition of A375 melanoma cells and found that the concentrations used did not strongly inhibit cell growth, even though the incubation time was up to 72 h. We used 8 μg/ml (0.8% w/v) arbutin because (i) this was the same concentration of kojic acid used 18 , because this concentration was lower than the safety recommendation of 1% in prescription human skin care products 36 ; (ii) this concentration inhibited cell growth less than 10% with no morphological change of cells; and (iii) it avoids changes in gene expression data resulting from the cell death response due to cytotoxicity from a high concentration of arbutin. Therefore, 8 μg/ml arbutin, which is safe for use on human skin, was used to study the genotoxic effect on the gene expression profile of A375 melanoma cells and for examining the differential gene expression and other side effects of altered signaling pathways for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations